Privacy, Data Protection, Risk, and Compliance in the Age of Generative AI Systems: A Systematic Mapping Study - Andrade, Richardson B. da S.; Rocha Filho, Geraldo Pereira; Marques, Gilmar dos Santos; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2026)
Research Context: Generative Artificial Intelligence (GenAI), particularly Large Language Models (LLMs), is advancing rapidly, raising concerns about privacy, data protection, risk management, and regulatory compliance. Despite transformative potential, adoption remains immature and constrained by ethical, technical, and legal limits. Scientific and/or Practical Problem: Organizations, developers, and end users face risks of privacy violations, re-identification, model inversion, and opacity. Current frameworks such as GDPR and Brazil’s LGPD struggle to address GenAI’s complexity, leaving gaps between technical safeguards and legal obligations. Proposed Solution and/or Analysis: We performed a systematic mapping focused on privacy-preserving mechanisms, risk management frameworks, and compliance models applicable to GenAI. We synthesize state-of-the-art approaches, their strengths and limitations, and assess how they enable trustworthy adoption. Related IS Theory: The study is grounded in information systems governance, privacy by design, and responsible AI, using sociotechnical lenses integrating technological, organizational, and regulatory perspectives. Research Method: Following a protocol, we searched four major digital libraries (ACM DL, IEEE Xplore, ScienceDirect, SpringerLink), applied inclusion and exclusion criteria, and conducted quality assessment. From 1,138 initial studies, 44 were analyzed in depth, and 15 met all thresholds. Summary of Results: We identify four principal categories of privacy techniques (differential privacy, federated learning, cryptographic approaches, synthetic data), five risk management frameworks (e.g., NIST AI RMF, MITRE ATLAS/AI Security), and compliance instruments (DPIA, conformity assessment, FRIA). Comparative analyses reveal trade-offs among robustness, scalability, and regulatory alignment. Contributions and Impact to the IS area: This study consolidates mechanisms for addressing privacy, risk, and compliance in GenAI, highlights gaps between technical safeguards and legal requirements, and distills design implications for trustworthy systems. It supports scholars and practitioners in engineering responsible AI and informs IS research agendas, organizational policies, and regulatory strategies for intelligent information systems.